Law Enforcement Against Racial And Ethnic Discrimination In Criminal Law Perspective - Barek Duli, Sesilia (CV. Inara, 2022)
Human life is always discrimination between humans and other humans. Human civilization always develops every age with various technologies and paradigms of people's lives that have an impact on certain superior and minority human groups. The Indonesian state still has a calculation in discriminatory behaviour in accordance with legal, economic and socio-cultural policies to provide preservation of certain political policies only, therefore the state must increase the perception of individual views to the community and certain groups. The State of Indonesia is committed to upholding and respecting human rights which have been regulated in the 1945 Constitution of the Republic of Indonesia. The 1945 Constitution has provided arrangements related to constitutional rights with the statement that everyone has the right not to get discriminatory treatment from others or certain parties. Discriminatory treatment in the State of Indonesia has a fairly high potential, due to the very large population of Indonesia and different ethnicities, races, cultures and languages, plus the level of education and the economy is relatively low. Therefore, a legal umbrella is needed to avoid the behaviour and consistency of people who discriminate against a person or group in the State of Indonesia by establishing laws and regulations as an effort to protect the law and increase public awareness in dealing with one another.